Efikasi Sosial Orangtua Dengan Stres Akademik pada Sekolah Dasar Menghadapi Pembelajaran Jarak Jauh Masa Covid-19 - Aini Nadhifah Purnamasari; Suroso Suroso; Niken Titi Pratitis (Jurnal Syntax Transformation, 2023)
This study aims to test empirically the relationship between self-efficacy and parental social support with the academic stress of elementary school students in the face of distance learning during the pandemic Covid-19. The subjects in this study were 284 high-class elementary school students, grades 4, 5 and 6 in Surabaya. The sampling technique used in this research is incidental sampling. The data analysis technique in this study used rank Spearman analysis to see the relationship between a variable and other variables. The first hypothesis in this study cannot be answered because the analysis used is the rank spearman. The results of the second study prove that the hypothesis which states that self-efficacy is negatively correlated with academic stress for elementary school students in the face of distance learning during the pandemic Covid-19 is accepted. This means that there is a significant negative relationship between self- efficacy and academic stress of elementary school students in the face of distance learning during the pandemic Covid-19. The results of the third study prove that the hypothesis which states that parental social support is negatively correlated with academic stress of elementary school students in the face of distance learning during the pandemic Covid-19 is accepted. This means that there is a significant negative relationship between parental social support and academic stress of elementary school students in the face of distance learning during the pandemic Covid-19.